Loss of imprinting and loss of heterozygosity on 11p15.5 in head and neck squamous cell carcinomas - Rainho, C. A.; Kowalski, L. P.; Rogatto, Silvia Regina [UNESP] (Wiley-Blackwell, 2001)
Background. IGF2 and H19 are reciprocal imprinted genes with paternal and maternal monoallelic expression, respectively. This is interesting, because IGF2 is known as a growth factor, and H19 encodes a RNA with putative tumor suppressor action. Furthermore, IGF2 and H19 are linked genes located on chromosome 11p15.5, a common site of loss of heterozygosity in human cancers.Methods. We performed an allelic-typing assay using a PCR-RFLP-based method for identification of heterozygous Informative cases in head and neck squamous cell carcinomas. Tumoral total RNA was extracted from each of the heterozygotes and further studied by RT-PCR analysis.Results. We detected the expression of the IGF2 gene in 10 of 10 informative cases. Two cases exhibited LOI of the IGF2 gene as evidenced by biallelic expression, and in another case, LOH was coupled with monoallelic expression of this growth factor. LOI for the H19 gene was observed in 1 of 14 informative samples analyzed. In this case, we also detected parallel mono-allelic expression of the IGF2 gene. Down-regulation of the H19 gene was observed in 10 of 14 cases.Conclusion. These findings support the hypothesis that H19 may be a tumor suppressor gene involved In head and neck carcinogenesis. Furthermore, our data showed that genetic and epigenetic chances at 11p15.5 could lead to abnormal expression of imprinted genes in HNSCC. (C) 2001 John Wiley & Sons, Inc.
Keywords: growth factor; tumor suppressor gene; loss of heterozygosity; genomic imprinting; head and neck carcinomas